Cover Image, Volume 28, Issue 12. (8th December 2017) - Tachibana, Motomi; Nishii, Nobuhiro; Morita, Hiroshi; Nakagawa, Koji; Watanabe, Atsuyuki; Nakamura, Kazufumi; Ito, Hiroshi
Abstract : On the cover : The cover image, by Motomi Tachibana MD et al., is based on the Original Article Exercise stress test reveals ineligibility for subcutaneous implantable cardioverter defibrillator in patients with Brugada syndrome, DOI: 10.1111/jce.13315 .